Personality and Hearing Acuity: Evidence From the Health and Retirement Study and the English Longitudinal Study of Ageing. Issue 9 (November 2019) - Stephan, Yannick; Sutin, Angelina R.; Caille, Pauline; Terracciano, Antonio
ABSTRACT: Objective: Several determinants of age-related hearing impairment have been identified, but little is known about the predictive value of psychological factors. The present study examined whether five-factor model personality traits are prospectively associated with hearing acuity in middle-aged and older adults. Methods: Participants were adults aged 50 to 97 years ( N > 10, 000) drawn from the Health and Retirement Study (2012–2016) and the English Longitudinal Study of Ageing (2010–2014). In each sample, personality, demographic factors, health-related behaviors, body mass index, and memory function were assessed at baseline, and objective hearing acuity was measured 4 years later. Results: In both samples, higher conscientiousness and openness were associated with better hearing acuity and lower risk of impairment, whereas neuroticism was associated with a higher risk of hearing impairment. In the Health and Retirement Study and English Longitudinal Study of Ageing, respectively, 1 standard deviation (1-SD) higher conscientiousness, 1-SD higher openness, and 1-SD lower neuroticism were related to 13% to 10%, 8% to 6%, and 10% to 13% lower likelihoods of hearing impairment, respectively. In both samples, additional analyses revealed that physical activity and memory mediated the association between personality and hearing. Conclusions: The present study provides robust evidence for an association between personality traits and hearing function. The findings broaden knowledge on risk and mitigating factors for age-related hearing impairment, which has implications for the quality of life of middle-aged and older adults.